Pitavastatin and Atorvastatin double-blind randomized comPArative study among hiGh-risk patients, including thOse with Type 2 diabetes mellitus, in Taiwan (PAPAGO-T Study). - Ping-Yen Liu; Liang-Yu Lin; Hung-Ju Lin; Chien-Hsun Hsia; Yi-Ren Hung; Hung-I Yeh; Tao-Cheng Wu; Ju-Yi Chen; Kuo-Liong Chien; Jaw-Wen Chen (PLoS ONE)
Background Evidence about the efficacy and safety of statin treatment in high-risk patients with hypercholesterolemia is available for some populations, but not for ethnic Chinese. To test the hypothesis that treatment with pitavastatin (2 mg/day) is not inferior to treatment with atorvastatin (10 mg/day) for reducing low-density lipoprotein cholesterol (LDL-C), a 12-week multicenter collaborative randomized parallel-group comparative study of high-risk ethnic Chinese patients with hypercholesterolemia was conducted in Taiwan. In addition, the effects on other lipid parameters, inflammatory markers, insulin-resistance-associated biomarkers and safety were evaluated. Methods and results Between July 2011 and April 2012, 251 patients were screened, 225 (mean age: 58.7 ± 8.6; women 38.2% [86/225]) were randomized and treated with pitavastatin (n = 112) or atorvastatin (n = 113) for 12 weeks. Baseline characteristics in both groups were similar, but after 12 weeks of treatment, LDL-C levels were significantly lower: pitavastatin group = -35.0 ± 14.1% and atorvastatin group = -38.4 ± 12.8% (both: p < 0.001). For the subgroup with diabetes mellitus (DM) (n = 125), LDL-C levels (-37.1 ± 12.9% vs. -38.0 ± 13.1%, p = 0.62) were similarly lowered after either pitavastatin (n = 63) or atorvastatin (n = 62) treatment. Triglycerides, non-high density lipoprotein cholesterol, and apoprotein B were similarly and significantly lower in both treatment groups. In non-lipid profiles, HOMA-IR and insulin levels were higher to a similar degree in both statin groups. Hemoglobin A1C was significantly (p = 0.001) higher in the atorvastatin group but not in the pitavastatin group. Both statins were well tolerated, and both groups had a similar low incidence of treatment-emergent adverse events. Conclusion Both pitavastatin (2 mg/day) and atorvastatin (10 mg/day) were well tolerated, lowered LDL-C, and improved the lipid profile to a comparable degree in high-risk Taiwanese patients with hypercholesterolemia. Trial registration ClinicalTrials.gov NCT01386853 http://clinicaltrials.gov/ct2/show/NCT01386853?term=NCT01386853&rank=1.